Language, meaning, sense and reference: Matthew"s passion narrative and Psalm 22 - Tilborg, S. van (Hervormde teologiese studies, 1988)
The passion narrative of Jesus as told by Matthew is a verbal enunciation which finds its place next to other passion narratives in which the narrator lets the protagonist use the words of the '1' person of Psalm 22 and in which the narrator describes internal and external conflicts with the words of the Psalm. Against the background of the Greek Septuagint and the Aramaic text in the Targum, parallel to what the hymnist of Qumran tries to do and the narrator of the story about Aseneth, based on the narrative as we find it in Mark, Matthew took Psalm 22 as anchor for his story. What is described in the Psalm, happens in the life and death of Jesus. To approach Jesus' passion more closely, Matthew used poetic language: words on words on words. The passion and death of Jesus has thus become literature, an ambiguous attempt to express the impossible. The question, 'how can one maintain today compassion against the forces of violence?', is the concern of the article.